Centering Indigenous Cultural Resurgence to Improve Ecological Restoration: Learnings from the Revitalization of Cultural Keystone Places of the Quw’utsun Peoples - Sachs, Nava S.; Martin, Tara G.; Grenz, Jennifer (Ethnobiology Letters, 2025)
Many places of ancestral and cultural importance to the Quw’utsun (Cowichan) Nation, have long been recognized by settlers as important contributors to biodiversity as habitat for rare and/or at-risk species and ecosystems. This recognition has resulted in numerous settler-led ecological restoration efforts of cultural keystone places such as Garry oak (Quercus garryana) meadows, Western red cedar (Thuja plicata) forests, and Pacific salmon (Oncorhynchus spp.) estuaries. While such efforts are well-intentioned, lack of understanding of pre-colonial baselines such as historical uses and stewardship practices and exclusion of cultural practices via the focus on fortress conservation have contributed to poor long-term restoration outcomes. Our research alongside Quw’utsun (Cowichan Tribes) and Spune’luxutth (Penelakut Tribe), is showing that centering cultural resurgence in restoration planning is a critical methodology that ensures projects respect the true history of lands, uphold community values, are culturally appropriate, protect Indigenous knowledges from misuse and misapplication, and ensure the reciprocal, human-land relationships required for long-term successful outcomes. Our learnings have broad implications for land restoration that suggest that finding ways to strengthen human relationships (Indigenous and non-Indigenous) to land, could provide the commitment and stewardship needed for lands to thrive into the future.